The role of information system quality in supporting decision-making in the economic enterprise: a case study of the Algerian Telecom Corporation for Mobilis - Chahid, Houda (Finance and Business Economies Review, 2019)
his study seeks to highlight the role of the information system on the effectiveness of the decision process, MOBILIS Foundation level answer to the problem at hand and verify hypotheses we conducted this study on a sample of employees, have been using descriptive analytical questionnaire was designed, composed of 22 paragraph to answer them to see how much information system on decision process, We have adopted in the analysis results and test hypotheses on statistical analysis software Spss and using a number of statistical methods: simple regression, analysis of variance and multiple regression by gradient method, the study found a range of results: significant differences Statistic between information system and effective decision making in Algeria for Mobile Communications Corporation.